2023
DOI: 10.1108/imr-10-2021-0308
|View full text |Cite
|
Sign up to set email alerts
|

Homefluencers' endorsement of millennial consumers' purchase intention in new normal

Abstract: PurposeThe purpose of this study is to examine how “homefluencers” sponsored posts on millennial consumers' purchase intention in the international marketing sphere can be impacted in the new normal by drawing on source credibility, parasocial interaction (PSI) and persuasion knowledge model (PKM) theory.Design/methodology/approachThis research applies structural equation modeling (SEM) and mediation analysis as the data analysis method using non-probability purposive sampling of a total of 217 local millennia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…Hair Jr et al (2010) have posited that purposive sampling is the most appropriate sampling technique when the scope of the study requires specific criteria to be met. Previous research in advertising has employed the purposive sampling technique (Ghosh & Islam, 2023; Hussain et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Hair Jr et al (2010) have posited that purposive sampling is the most appropriate sampling technique when the scope of the study requires specific criteria to be met. Previous research in advertising has employed the purposive sampling technique (Ghosh & Islam, 2023; Hussain et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This method allows more responses to be collected quickly and effectively (Saunders et al, 2012). This method has been used in other studies on the same topic (see, for example, Chaihanchanchai et al, 2024 andGhosh &Islam, 2023).…”
Section: Data Collection and Samplementioning
confidence: 99%
“…One way to use social media to achieve marketing goals is by collaborating with social media influencers, also known as social media influencer marketing (De Veirman et al, 2019;Haenlein et al, 2020). Recent studies have shown that "Generation Z" or "millennial" consumers tend to shun traditional media in favor of online content generated by influencers (Cabeza-Ramírez et al, 2022;Ghosh and Islam, 2023;Mostafa, 2021;Panopoulos et al, 2023;Sfodera et al, 2020).…”
Section: Introductionmentioning
confidence: 99%